2017
DOI: 10.1002/hbm.23543
|View full text |Cite
|
Sign up to set email alerts
|

Tuning face perception with electrical stimulation of the fusiform gyrus

Abstract: The fusiform gyrus (FG) is an important node in the face processing network, but knowledge of its causal role in face perception is currently limited. Recent work demonstrated that high frequency stimulation applied to the FG distorts the perception of faces in human subjects (Parvizi, et al., 2012). However, the timing of this process in the FG relative to stimulus onset and the spatial extent of FG's role in face perception are unknown. Here, we investigate the causal role of the FG in face perception by app… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
23
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
3
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 34 publications
(24 citation statements)
references
References 56 publications
(90 reference statements)
1
23
0
Order By: Relevance
“…As presented in the introduction, the right hemispheric dominance for individual face discrimination but not for generic face categorization in preschool children is in line with a variety of observations made in adults, showing either enhanced or exclusive right lateralization when individuating faces as compared to the categorization of faces as faces. This is the case for EEG measures, either obtained in standard ERP paradigms (e.g., Jacques & Rossion, ) or during FPVS (Liu‐Shuang et al, ; Rossion et al, ) and, most importantly, when considering the interruption of function either following brain damage (e.g., Rossion et al, ), transcranial magnetic stimulation over the right lateral occipital cortex (Ambrus et al, ; Pitcher et al, ; Solomon‐Harris et al, ) or intracranial stimulation in the right inferior occipital gyrus and fusiform gyrus (Chong et al, ; Jonas et al, , ; Keller et al, ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…As presented in the introduction, the right hemispheric dominance for individual face discrimination but not for generic face categorization in preschool children is in line with a variety of observations made in adults, showing either enhanced or exclusive right lateralization when individuating faces as compared to the categorization of faces as faces. This is the case for EEG measures, either obtained in standard ERP paradigms (e.g., Jacques & Rossion, ) or during FPVS (Liu‐Shuang et al, ; Rossion et al, ) and, most importantly, when considering the interruption of function either following brain damage (e.g., Rossion et al, ), transcranial magnetic stimulation over the right lateral occipital cortex (Ambrus et al, ; Pitcher et al, ; Solomon‐Harris et al, ) or intracranial stimulation in the right inferior occipital gyrus and fusiform gyrus (Chong et al, ; Jonas et al, , ; Keller et al, ).…”
Section: Discussionmentioning
confidence: 99%
“…Likewise, transcranial magnetic stimulation over the right lateral occipital cortex impairs individuation of faces (Ambrus, Dotzer, Schweinberger, & Kovács, ; Pitcher, Walsh, Yovel, & Duchaine, ; Solomon‐Harris, Mullin, & Steeves, ) but not the categorization of a face as a face (Solomon‐Harris et al, ). In the same vein, transient failures to individuate faces have been observed following intracranial stimulation in the right but not the left face‐selective regions (Jonas et al, , ), while difficulties at categorizing visual stimuli as faces can be observed following stimulation in either the left or right hemisphere face‐selective regions (Chong et al, ; Keller et al, ). In EEG studies, indexes of individual face discrimination usually found using stimulus repetition are strongly right lateralized, whether they are obtained in standard ERP designs (i.e., on the N170, Jacques & Rossion, ; Rossion, ) or with EEG frequency‐tagging (Liu‐Shuang, Norcia, & Rossion, ; Rossion & Boremanse, ).…”
Section: Introductionmentioning
confidence: 98%
“…changes in brain excitability at baseline and after stimulation, we performed corticocortical evoked potential (CCEP) mapping 27 . CCEPs have been used to predict the onset of ictal events 28 , examine the functional brain infrastructure 29,30,31,32 , and causally examine the fronto-parietal 33 , hippocampal 34,35 , visual 36 , and language 37 networks. Prior to and immediately after repetitive stimulation, we applied bipolar electrical stimulation (biphasic pulses at 100 µs/phase) with a 1s inter-stimulation interval (ISI).…”
Section: Pre/post-stimulation Ccep Mapping (Effective Connectivity) mentioning
confidence: 99%
“…described facial hallucinations (isolated eyes, single or multiple faces), without looking at faces, following stimulation of distributed face‐selective sites along the posteroanterior axis of the VOTC. More recent ECoG studies have focused on the latFG, reporting facial perceptual distortions in the right but not in the left hemisphere, or deficits in face categorization …”
Section: Summary and Challenges Ahead In Ieeg Mapping Of Face And Vismentioning
confidence: 99%